The Relationship Of The Ability To Solve Problems To Cognitive Failures Of University Students - Gomaa Abdullah, Hanan (Opción, 2019)
Solving the problem is a cognitive mental activity directed, but rather, this ac- tivity is organized according to organized and purposeful methods designed, and in this type of thinking there is an organization and representation of previous experiences and elements of attitudes that the individual is exposed to including in order to achieve the goal of overcoming obstacles and solving problems (Mahmoud, 2001: 318), the study (Odeh, 1996) showed that there are no differences in solving the problem among students by type, and that there are no differences according to academic specialization and that univer- sity students have skills to solve problems, and a study (Justice, 2013) showed that there are significant differences Statistically in my approach to problem solving (orientation towards the problem, and control exactly Personal) in fa- vor of females, and the existence of differences in methods of problem solving (directed towards problem solving, creative problem solving, confidence in problem solving and reluctance, and feet) in favor of human specialization. Some classify problem solving within cognitive modification methods and in- cludes developing problem-solving skills through developing appropriate gen- eral strategies to deal with problems and finding solutions in the field of facing them, and problem solving in the literature of psychotherapy is described as cognitive behavior, because it tries to develop general methods of dealing with problems instead From focusing on a specific cognitive process, it is believed that following one method of the situation leads the individual to his failure to solve the problem in an organized manner (Al-Khatib, 2003: 349), that the occurrence of individuals in many cognitive failures occurs in their daily lives such as forgetting names and failure to notice signs The Road Difference with people and distraction and things were inadvertently lost, and scientists called these errors and errors (Cognitive Failures), and a study (Daniliel & Jessica, 2010) showed that attention gaps reflected the occurrence of cognitive failure and also found that attention gaps were positively linked to the occurrence of cognitive failures, and reached Shipman & Shipman (2012) study indicates a weak relationship between cognitive dissonance and cog- nitive failures and working memory with a correlation between working memory disorders and cognitive failures. The researcher felt the problem of research through their experience of education, personal experience and daily observations about the existence of many study problems and knowl- edge failures, especially among university students who are essential pil- lars of society.